WAKAF PRODUKTIF SEBAGAI INSTRUMEN KESEJAHTERAN SOSIAL DAN PEMBERDAYAAN EKONOMI UMAT (POTENSI DAN TANTANGAN) - Abd. Kadir Arno (Dinamis : Journal of Islamic Management and Bussiness, 2018)
As a religious institution with potential economic benefits, effective and efficient waqf empowerment for productive purposes is a must. So there must be an effort to manage the productive waqf, so it can provide a solution of what is expected that can prosper the community then it needs optimal management of existing waqf objects. The management of endowments in Indonesia is faced with various challenges, among others: a) development of waqf by nazhir more on the protection of waqf property not by the utilization of waqf; (b) Muslims' understanding of waqf is lacking; (c) the limited amount of government support in the form of budgets to facilitate the wakaf movement and the provision of services for the administration of waqfs; (e) the lack of activities that educate and socialize productive wakaf to the Muslim community, this condition has an impact on the low awareness of waqf; and (f) the establishment and distribution of wakaf institutions in regions has not considered the potential of wakaf in each region